2021
DOI: 10.1093/nop/npab046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neurological function using the National Institute of Health Stroke Scale in patients with gliomas

Abstract: Background The evaluation of treatment response in patients with gliomas is performed using the Response Assessment in Neuro-Oncology (RANO) criteria. These criteria are based on cerebral magnetic resonance imaging (MRI), steroid use and neurological function. However, a standardized tool for evaluating neurological function was lacking. We compared changes in the National Institute of Health Stroke Scale (NIHSS) to changes in the RANO categories to determine the relationship between clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In our study, we found that NIHSS scores were significantly decreased in patients receiving Danhong injection plus Western medicine. The minimal clinically important difference (MCID) of the NIHSS score in stroke patients was considered an increase or decrease of two points, that is, a change in the NIHSS score of more than two points suggests clinical importance of the differences ( Chang and Xu., 2011 ; Neurology Chapter of China Association of Chinese Medicine et al, 2020 ; Zeitlberger et al, 2021 ). The change of the NIHSS score in our study was 4.21 points between the experiment group and the control group, which suggested that Danhong injection added to Western medicine would be more beneficial in reducing the severity of ischemic stroke and improving neurological status than Western medicine alone for ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that NIHSS scores were significantly decreased in patients receiving Danhong injection plus Western medicine. The minimal clinically important difference (MCID) of the NIHSS score in stroke patients was considered an increase or decrease of two points, that is, a change in the NIHSS score of more than two points suggests clinical importance of the differences ( Chang and Xu., 2011 ; Neurology Chapter of China Association of Chinese Medicine et al, 2020 ; Zeitlberger et al, 2021 ). The change of the NIHSS score in our study was 4.21 points between the experiment group and the control group, which suggested that Danhong injection added to Western medicine would be more beneficial in reducing the severity of ischemic stroke and improving neurological status than Western medicine alone for ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…In strokes, a two-point change in the NIH-SS is considered meaningful, but we here used any change for evaluation. Meanwhile, it has been shown that the NIH-SS does not correlate to changes in the RANO criteria and was too insensitive to recognize changes in neurological function in the management of GBM patients [14]. However, the NIH-SS is still in use in ongoing neuro-oncological trials, for example, the randomized controlled SAFE trial [23], which also use one-point changes as a relevant cut-off value.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the extent of neurological deficits for later comparison at different time points, we used the NIH-SS as a measurement as the recently proposed and validated Neurological Assessment in Neuro-Oncology scale (NANO-scale) has not been introduced at the time the study was planned and conducted [12]. The NIH-SS score has been used in other studies investigating GBM [13,14]. This quantitative measure of neurological deficits evaluates 15 domains, including consciousness, aphasia and dysarthria, hemianopia and extraocular movement, hemiparesis, sensory loss, ataxia, and neglect.…”
Section: Patient Population and Timelinementioning
confidence: 99%